2‐Hydroxy‐4‐benzyloxylimine Resveratrol Derivatives as Potential Multifunctional Agents for the Treatment of Parkinson's Disease. (24th January 2023) - Cao, Zhongcheng; Zhang, Tianlong; Fu, Xianwu; Wang, Xingyue; Xia, Qian; Zhong, Lei; Zhu, Jiang
Abstract: A series of 2‐hydroxy‐4‐benzyloxylimine resveratrol derivatives was designed, synthesized and evaluated as multifunctional agents for the treatment of Parkinson's disease. The results revealed that most derivatives possessed good multifunctional activities. Among them, representative compound ( E )‐5‐[(4‐fluorobenzyl)oxy]‐2‐[(4‐hydroxyphenyl)imino]methylphenol (7 h ) exhibited excellent MAO‐B inhibition (IC50 =8.43×10 −3 μM) and high antioxidant activity (ORAC=3.45 Trolox equivalent). Additionally, 7 h displayed good metal chelating ability, appropriate blood–brain barrier (BBB) permeability, significant neuroprotective effect, and great anti‐neuroinflammatory activity. Furthermore, 7 h can also ameliorate 1‐methyl‐4‐phenyl‐1, 2, 3, 6‐tetrahydropyridine (MPTP)‐induced Parkinson's disease symptoms in mice. Therefore, compound 7 h was found to be a promising candidate for further development against PD. Abstract : The combination of ortho hydroxyimine resveratrols with aryl benzyl ethers afforded 2‐hydroxy‐4‐benzyloxyimine resveratrol derivatives. Representative compound 7 h exhibited good MAO‐B inhibition, antioxidant activity, biometal chelating ability, neuroprotective and anti‐neuroinflammatory activities. In addition, 7 h possesses appropriate blood‐brain barrier permeation and can attenuate the motor deficits induced by 1‐methyl‐4‐phenyl‐1, 2, 3, 6‐tetrahydropyridine (MPTP).